GADGET DEPENDENCY AND ITS IMPACT ON ACADEMIC PERFORMANCE: A STUDY AMONG HIGHER EDUCATION STUDENTS - Asmahanim Haji Mohamad Yusuf; Mohd Nur Fitri Mohd Salim; Mohamad Safwat Ashahri Mohd Salim; Alya Sabrina Rusmi; Wan Nur Dieyana Airien Wan Amri; Nurul Farhanah Mohd Sobirin; Nurina Izzati Mohamad Rohaizad (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The growing use of gadgets in educational settings has significantly influenced students’ academic experiences in various ways. This study investigates the dependency on gadgets in classrooms among students at a Malaysian university, focusing on its frequency and correlation with academic performance. A sample of forty students from the Faculty of Computer and Mathematical Sciences was selected through purposive sampling. Data collection was performed using a questionnaire distributed via WhatsApp and Telegram, followed by analysis using SPSS software. Findings revealed that while most students frequently use gadgets during lectures, there is no significant correlation between gadget usage and their academic performance, measured by GPA and CGPA. However, students perceived that gadget positively contributed to their academic engagement and efficiency. The results suggest that while gadgets are valuable for accessing educational resources, their use must be balanced to prevent distraction. The study concludes with recommendations for educators and institutions to optimise the integration of technology into classroom environments, promoting both responsible gadget use and effective learning outcomes.